Critical Analysis of Raja Rao’S Novel-Kanthapura: Exploring Nationalism and Metaphysical Concepts in Raja Rao's Kanthapura (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Raja Rao, the famous Indian English writer, was born on 8th November 1908 in Hassan, Karnataka. Nationalism was a theme of many of his novels. His novel Kanthapura is an account of Mahatma Gandhi's teachings. It is the story of national struggle through the view point of a villager in Karnataka. In the words of a critic- "Raja Rao is one of those enigmatic writers whose novels have been received with wholehearted commendation by such critics as C.D. Narasimhaiah and Edwin Thumboo and with as intense or bemused a condemnation by many critics in India and by the reviewers of Time and the New York Times abroad. Rao is a powerful writer. He is profoundly metaphysical in the way he thinks and feels, and he has a scholarly background, an intimate familiarity with primary texts of Hindu, Bhuddhist, and Christian philosophies; his mastery of English vocabulary is indisputable (as is his mastery of French), and his prose is often scintillating poetry. ... All of Rao's novels explore philosophical concepts."